BODY COMPOSITION OF STATE PUBLIC STUDENTS SCHOOLS IN ALTA FLORESTA D’ OESTE – RO (Fiep Bulletin - online, 2012)
This paper has like objective verifying whether body composition of schoolchildren in Alta Floresta D’Oeste - RO is within the predetermined standards for their age, using the protocol of Lohman (1986, 1988) for anthropometric measures and body mass index (IMC). We examined 279 children from 07 to 12 years who are properly registered and attending the state schools, with 139 males (49,9%) and 140 females (50,1%). The study used the direct method of field with descriptive design using cross was lifted with statistical approach quantitative. Comparing the values of central tendency of the weight, we found that there were no significant differences between boys and girls of the same population. 5,4% of the sample is divided into 5,8% male and 5% on the female sample general. As the classification of overweight was observed in this study that the percentage on the sample was 22,2% of the total, is divided into 19.4% males and 25% female. As the classification obesity, the incidence of the sample was 5.4%, boys accounted for 4.3% and 6,5% girls. The largest percentage of the sample was concentrated in the classification standard that represented 67% of the sample is divided into 70,5% males and 63,5% female. It was concluded that the body composition of students corresponds to the appropriate indexes. Well, most students fall within the classification of IMC as normal and fat percentage with appropriate classification.
Keywords: body composition; students and anthropometry